Frequency of delta F508 in a Mexican sample of cystic fibrosis patients. Issue 6 (June 1993) - Orozco, L; Salcedo, M; Lezana, J L; Chávez, M; Valdez, H; Moreno, M; Carnevale, A
Abstract : This paper reports the frequency of the delta F508 mutation in a cohort of 50 Mexican patients with cystic fibrosis (CF). The mutation was detected by PCR mediated site directed mutagenesis. delta F508 was found in 39% of CF chromosomes, a frequency lower than that reported in Argentina and Spain. The high rate of CF cases who die undiagnosed, the ethnic origin of Mexican populations, and the limited number of cases studied could account for the low frequency of the delta F508 mutation found in this preliminary report.